The Factorization Method for Electrical Impedance Tomography Data from a New Planar Device - Mustapha Azzouz; Martin Hanke; Chantal Oesterlein; Karl Schilcher (International Journal of Biomedical Imaging)
We present numerical results for two reconstruction methods for a new planar electrical impedance tomography device. This prototype allows noninvasive medical imaging techniques if only one side of a patient is accessible for electric measurements. The two reconstruction methods have different properties: one is a linearization-type method that allows quantitative reconstructions; the other one, that is, the factorization method, is a qualitative one, and is designed to detect anomalies within the body.